Pandemic Aftershock: Revisiting Consumers’ Risk Perception Attitude and Perceived Safety towards an Audience-Centered Marketing Paradigm - AL-Sahouly, Ibrahim (Archives of Business Research, 2021)
Abstract Purpose The purpose of this empirical research is to empirically investigate the effect of Covid-19 crisis on Egyptians’ risk perception attitude, perceived safety and local travel intentions inside Egypt for the aim of reaching significant marketing insights and recommendation to benefit the tourism sector during Covid-19 pandemic. Those marketing insights can help prepare citizens to deal with the crisis challenges for the objective of normalizing everyday practice, maintain productivity and help protect the stability of the community. Design/methodology/approach This research adopts the variables of the Extended Parallel Process Model (EPPM), which provides a useful framework to understand how individuals respond to crisis/risk. This research empirically investigates the current insights, concerns and needs of 300 samples from the Egyptian community for the aim of reaching a practical method of normalization; thus, bridging what the researcher would like to call “the blind spot” or gaps of actions between decision makers and citizens. This research applies quantitative research method. Data were collected online. It is significant to pinpoint that this empirical investigation adopts the Extended Parallel Process Model (EPPM), which provides a useful framework to understand how individuals respond to crisis/risk communication messages for the purpose of investigating the research hypotheses; thus, this empirical study does not aim to extend nor to present a conceptual framework for the adopted Extended Parallel Process Model (EPPM) within the Egyptian milieu. Findings The research findings suggest new marketing implementations for overcoming the challenges facing the local tourism sector in Egypt due to Covid-19 pandemic crisis, and further recommends an audience-centered paradigm in marketing and communicating promotional messages. Originality/value To date, limited empirical research has investigated Egyptian tourists’ insights for sustaining the internal tourism sector in Egypt during normal and crisis times. This research is considered valuable to decision makers, marketers and academics alike as it provides up- to- date marketing insights and empirical results for the aim of normalizing the internal tourism practices in Egypt after the pandemic shock and even during the consecutive waves of Covid-19.